Compreensão de leitura e habilidades de processamento auditivo em crianças - Albuquerque, Diana Babini Lapa de (2007)
The disorders of the auditory processing (APD) intimate are related to the difficulties in the verbal language and writing. The hearing is the main way of entrance for the acquisition of the verbal language and the learning of the writing, in turn, is based on the standards of the orality. In such a way, some studies already had demonstrated to the relation between the DPA and the difficulties in the learning of the reading and the writing. However, still a gap exists to be explored, that it consists in the investigation of as the Auditory Processing (AP) is related with the important abilities for the pertaining to school success, as is the case of the reading comprehension. The present study it has, therefore, the objective to investigate the relation between the comprehension of reading and the abilities of auditory processing in children. 28 children had participated of the study, of both sexs, attending a course 2ª and 4ª series of the elementary school of a public school of Recife. The participants had been submitted to a task of evaluation of level of reading understanding and the following tests of AP: test of sonorous localization, sequential memory for verbal and non-verbal sounds, speaks filtered, dichotic test of dissyllabics and directed listening non-verbal. The results had evidenced that did not have difference significant statistics between the levels of comprehension of reading of the children of 2ª series to the children oh 4º series, having, however, an advance in the comprehension of reading to the measure that occurred an advance in the age and the schooling. As to the AP tests carried was only found difference significant statistics between the series in the dichotic test of directed listening non-verbal (p<.05), in which the ability of binaural separation was evaluated. It is important to detach here that some of the children who if had classified in the levels most advanced of reading comprehension had presented alteration in the ability of investigated binaural separation in this test. It was still verified a predictive effect of the ability of binaural separation on the reading comprehension. The results suggest that the reading comprehension is an independent process of the abilities of auditory processing and that the different abilities related to the AP can present different results.